The Concept of Green Human Resource Management in Industry - Adif, Riandy Mardhika; Na`am, Jufriadif; Nazir, Novizar (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2020)
The integration of environmental management into Human Resource Management (HRM) is called Green HRM. There is a growing need for the application of Green HRD in industry. The objective of this review is to explore green human resource management practices of organizations in the industry based on the existing literature. Based on this review, it is concluded that by understanding and increasing the scope and depth of green HRM practices, organizations can improve their environmental performance in a more sustainable manner than before. The green HRM practices are more powerful tools in making organizations and their operations in industry green. The green performance, green behaviors, green attitude, and green competencies of human resources can be shaped and reshaped through the adaptation of green HRM practices.